The Role of Islamic Guidance and Counseling Teachers in Improving the Emotional Intelligence of MTs Negeri 2 Surakarta Students - Muhammad Syahreza Pahlevi; Hafidz (Didaktika: Jurnal Kependidikan, 2024)
This study aims to investigate the role of Islamic guidance and counseling teachers in improving students' emotional intelligence in MTs Negeri 2 Surakarta. Emotional intelligence has a significant impact on student development, and this study focused on implementing Islamic guidance and counseling practices to strengthen students' emotional aspects. This research design is a case study with a qualitative approach used in this research method. Data were collected through in-depth interviews with Islamic guidance and counseling teachers, observation, and analysis of related documents. The main respondents were MTs Negeri 2 Surakarta students who participated in the Islamic guidance and counseling program. The results showed that Islamic guidance and counseling teachers play a significant role in improving students' emotional intelligence. They involve students in group guidance activities, provide personalized counseling, and integrate Islamic values in the learning process. These efforts help students develop a better understanding of emotions, improve their ability to manage stress, and strengthen their social relationships. In addition, the study also highlights some of the challenges faced by Islamic guidance and counseling teachers, including limited time and resources. Therefore, better support from schools and governments is recommended to strengthen this role in improving students' emotional intelligence. In conclusion, MTs Negeri 2 Surakarta Counseling Guidance Teachers play a very important role in constructing students' emotional intelligence at MTs Negeri 2 Surakarta. This research contributes to further understanding how the practice of Islamic guidance and counseling can have a positive impact on students' emotional development, as well as providing suggestions for further improvement in its implementation.